Academic Self-Efficacy and Aspiration Goals Among Muslim High School Students: The Role of Problem-Solving and Self-Awareness - Yendi, Frischa Meivilona; Firman, Firman; Syukur, Yarmis; Ifdil, Ifdil; Putra, Ade Herdian (Islamic Guidance and Counseling Journal, 2025)
This study aims to analyze the relationship between academic self-efficacy and aspirational goals of Muslim high school students in Indonesia, as well as the moderating role of problem-solving and self-awareness. The background of this research is based on the importance of aspiration in determining the direction of students' education and careers. The research design employed a quantitative correlational approach to examine the relationships among the study variables. The research participants consisted of Muslim high school students selected using purposive random sampling. A total of 608 participants were involved, comprising 41.45% male and 58.55% female students, with ages ranging from 15 to 18 years. The research instruments included the academic self-efficacy, problem-solving, self-awareness, and aspiration goals scale, which were measured by the Likert scale. Data collection was conducted through both online surveys and direct administration at all participating schools, allowing students to choose the method based on their accessibility and preference. The data analysis technique used the Partial Least Squares Structural Equation Model (PLS-SEM). The results indicated that academic self-efficacy positively influenced aspiration goals, and that problem-solving and self-awareness significantly moderated this relationship. The proposed research model demonstrated good fit criteria. PLS-SEM is a variance-based structural equation modeling technique that is suitable for analyzing complex models and predictive research frameworks. The conclusion of this study confirms the importance of improving self-efficacy to encourage students' aspirations. Suggestions are given for developing intervention programs that can improve the self-efficacy and aspirations of Muslim high school students in Indonesia.